Analisis kesulitan belajar matematika peserta didik dalam menyelesaikan soal cerita di sekolah dasar - Niken Nur Amelia; Riyadi Riyadi; Siti Wahyuningsih (Universitas Sebelas Maret, 2024)
Abstract. The purpose of the research are to (1) describe the types of student’s mathematics learning difficulties of grade 5th B Karang Elementary School in solving story problems using Newman theory analysis for the 2023/2024 academic year, (2) describe the factors causing student’s mathematics learning difficulties in solving story problems. The material studied in this study is multiplication and division of decimal numbers. This research uses the qualitative and case study type research. The research subjects in this study were five students of 5th B Karang Elementary School. Validity tests in this study used tricoagulation techniques and time. Data collection techniques are carried out through tests, interviews, and documentation studies. The data analysis used is Miles and Huberman's data analysis. The results showed that students had: (1) reading difficulties by 4.4%, (2) comprehension difficulties by 14.4%, (3) transformation difficulties by 26.6%, (4) process skills difficulties by 25.9%, (5) difficulty writing final answers by 28.5%. The factors that cause student’s learning difficulties, include: 1) students cannot read mathematical units, 2) students do not know how to understand the problem, 3) students do not know how to make and the importance of writing mathematical models and choose the wrong calculation operations, 4) students do not understand the sequence of doing calculations by multiplication and division of decimal numbers and do not recorrect the results, 5) difficulty at the calculation stage, forgetting to determine the location of the comma, and not knowing the importance of writing conclusions and how to make them.Keywords: maths learning difficulties, students, story problems, Newman procedure